Genome-wide characterisation of the three amino acid loop extension gene family of watermelon in response to abiotic stresses - Qiu, Zongqing; Dong, Jing; Chen, Liqin; Zhao, Lijun; Hu, Liangliang; Wang, Huilin (Frontiers in Plant Science, 2025)
IntroductionThe TALE gene family acts as key regulators of plant growth, development, and stress adaptation. However, systematic characterization of this family in watermelon (Citrullus lanatus L.), an economically important cucurbit crop susceptible to abiotic stresses like drought and cold, is lacking. This gap hinders understanding of watermelon’s stress-responsive mechanisms and the breeding of stress-resilient varieties.MethodsClTALE genes were comprehensively identified using the watermelon genome database. Bioinformatics analyses (phylogenetic classification, genomic structure annotation, conserved motif detection, cis-acting element prediction) were performed. Protein-protein interactions were inferred via STRING. qRT-PCR detected expression profiles under drought, low potassium (LK), and melatonin + cold (MT+CT) treatments. Subcellular localization of candidate genes was analyzed by transient expression, and yeast heterologous expression verified stress tolerance under PEG-simulated drought.ResultsA total of 22 ClTALE members were identified, clustering into seven subclades (KNOX-I/STM, KNOX-II, BELL-I to BELL-V). Their promoters contain abundant hormone-related (abscisic acid, jasmonic acid) and abiotic stress-related (drought, cold) cis-acting elements. ClTALE proteins may interact with core growth and development transcription factors. ClTALE2, 3, 8, 11, and 20 were significantly upregulated under drought; ClTALE2 and 3 showed cross-response to LK and MT+CT. ClTALE3 localizes to the nucleus, and its overexpression enhanced yeast tolerance to PEG stress.DiscussionThis study is the first systematic characterization of the watermelon ClTALE family, clarifying its genomic features, evolutionary relationships, and stress-responsive patterns. ClTALE2 and 3 (especially ClTALE3) exhibit potential as key stress adaptation regulators. These findings provide a theoretical basis and genetic resources for elucidating watermelon’s stress-resistance mechanisms and breeding stress-tolerant varieties.